2003
DOI: 10.1080/jmf.13.3.163.170
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac defects in chromosomally normal fetuses with increased nuchal translucency at 10–14 weeks of gestation

Abstract: Euploid fetuses with increased nuchal translucency thickness have a significantly increased risk of cardiac defects. This is a marker of different types of heart anomalies and constitutes an additional indication for targeted fetal echocardiography. Most of the cardiac defects can be detected by fetal echocardiography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 21 publications
0
16
0
2
Order By: Relevance
“…This has prompted research to explore the feasibility of advancing cardiac screening to the first trimester in high‐risk patients. Consequently an increasing number of studies on nuchal translucency and CHD have been published during the past decade13–16. A recent review of previous results concluded that, in experienced hands, early fetal echocardiography (EFE) before 14 weeks' gestation is feasible and accurate in diagnosing most major CHDs, potentially achieving a sensitivity of around 85% and a specificity approaching 100%17.…”
Section: Introductionmentioning
confidence: 99%
“…This has prompted research to explore the feasibility of advancing cardiac screening to the first trimester in high‐risk patients. Consequently an increasing number of studies on nuchal translucency and CHD have been published during the past decade13–16. A recent review of previous results concluded that, in experienced hands, early fetal echocardiography (EFE) before 14 weeks' gestation is feasible and accurate in diagnosing most major CHDs, potentially achieving a sensitivity of around 85% and a specificity approaching 100%17.…”
Section: Introductionmentioning
confidence: 99%
“…This study also suggested that the incidence of CHD dramatically increased with increasing NT. Other investigators have confirmed these initial observations and provided further evidence to support this association9–16. In chromosomally normal fetuses in which NT ≥ 99th centile (i.e.…”
Section: Increased Nt and (Structural) Heart Abnormalitiesmentioning
confidence: 59%
“…In chromosomally normal fetuses in which NT ≥ 99th centile (i.e. NT ≥ 3.5 mm) the risk of a major cardiac abnormality is around 5–10%10, 11, 15, 17. This is unquestionably higher than the risk observed in many families traditionally referred for fetal echocardiography.…”
Section: Increased Nt and (Structural) Heart Abnormalitiesmentioning
confidence: 94%
“…Recent studies have suggested the potential role of increased NT thickness [33][34][35][36][37][38][39] or an abnormal ductus venosus (DV) flow pattern [40][41][42] at early pregnancy as a screening tool for CHD, in addition to its role in screening for chromosomal defects ( Figure 6). The risk of CHD after the finding of an increased NT in chromosomally normal fetuses seems to vary between 4 and 9% [43,44]. Hyett et al reported that about 55% of major CHDs were associated with a fetal NT thickness above the 95th centile at 10-14 weeks of gestation [33].…”
Section: Identification Of New Markers Of Congenital Heart Defectsmentioning
confidence: 95%